2021
DOI: 10.1021/acsfoodscitech.1c00394
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pea and Potato Protein Microparticles on Texture and Sensory Properties in a Fat-Reduced Model Milk Dessert

Abstract: With increasing diet-related health issues and awareness of climate change, the demand for sustainable protein-based fat replacer increases. In this study, the impact of the incorporation of pea and potato protein microparticles in fat-reduced (−50%) milk desserts was tested texturally and sensorically. The incorporation of pea protein microparticles led to a harder texture and higher adhesiveness and creaminess, whereas these attributes were decreased by the incorporation of potato protein microparticles. Nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In materials with strong gel-like characteristics, the G′ is nearly independent of angular frequency ( García-Ortega et al, 2021 ). Accordingly, Tanger et al (2021) observed a lower frequency dependence and a higher G′ in a model milk dessert where 50% of fat was replaced by pea protein and reported more gel-like characteristics caused by more stabilizing interactions in these products. Additionally, researchers have elucidated the role of milk fat in rheological characteristics of dairy products.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In materials with strong gel-like characteristics, the G′ is nearly independent of angular frequency ( García-Ortega et al, 2021 ). Accordingly, Tanger et al (2021) observed a lower frequency dependence and a higher G′ in a model milk dessert where 50% of fat was replaced by pea protein and reported more gel-like characteristics caused by more stabilizing interactions in these products. Additionally, researchers have elucidated the role of milk fat in rheological characteristics of dairy products.…”
Section: Resultsmentioning
confidence: 92%
“…Use of HPH to increase water-binding capacity and gel firmness has been reported in different products such as acid-coagulated yoghurts ( Serra et al, 2009 ), fresh cheeses ( Zamora et al, 2011 ), and yoghurts prepared from soymilk ( Ferragut et al, 2009 ). Tanger et al (2021) observed that incorporation of pea protein microparticles led to an increase in hardness, adhesiveness, and creaminess in the fat-reduced model milk dessert. Thus, the ability of the UST to alter the rheological properties of dispersions could also be utilized in development of fat-reduced products such as low-fat ice cream, salad dressings, yoghurt, sauces, and others.…”
Section: Resultsmentioning
confidence: 97%
“…The intermolecular forces of heat-induced composite gels were analyzed using the method described by Tanger et al and Tanger et al [ 30 , 31 ] with some modifications. In blocking the different forces between gel protein molecules by different chemical reagents as a principle, the following was done.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, XG delays soy protein molecular movement, stabilizes the protein, and protect aggregation in the ice cream matrix. Tanger et al (2022) produced fat-reduced milk desserts by substituting 50% (w/w) of fat content in recipe by pea and potato protein microparticles. It was found that the pea protein enhanced gelling properties, higher adhesiveness, and creaminess in a better manner than the potato protein.…”
Section: How Do Probiotics Lower Cholesterol Levels and Reduce Satura...mentioning
confidence: 99%
“…Moreover, addition of plant oil, plant protein, or fish protein negatively affected the sensory properties, such as fishiness, grassiness, greenishness, and bean-like off-notes, of plant proteins. Therefore, these challenging problem must be investigated in the future studies (Mayengbam et al, 2021;Shi and Li, 2021;Tanger et al, 2022).…”
Section: How Do Probiotics Lower Cholesterol Levels and Reduce Satura...mentioning
confidence: 99%